Case Report: Multidisciplinary Approach for a Rare Case of Thymic Vascular Malformation - Raveglia, Federico; Moneghini, Laura; Cariati, Maurizio; Baisi, Alessandro; Guttadauro, Angelo; Cioffi, Ugo; Scarci, Marco (Frontiers in Surgery, 2021)
We report the rare case of a 2.5 cm in size mass diagnostic for residual thymus associated with venous vascular malformation (ISSVA classification, 2008) in a 58 years old man. Diagnosis was obtained only after surgical removal that was complicated by a sudden massive bleeding (about 1,500 cc) requiring emergency conversion to median sternotomy. Difficulty in preoperative diagnosis, rarity of histologic pattern, and surgical challenges make this case very interesting for surgeons, pathologists and radiologist. Our message, dealing with mediastinal masses, is: (a) differential diagnosis between the more frequent solid antero-superior mediastinal tumors and vascular malformation should be always considered (b) preoperative angiography should always be performed in case of uncertain diagnosis (c) coil embolization should always be considered to reduce potentially fatal bleeding (d) histologic differentiation with other thymic neoplasms must be always considered.